2020
DOI: 10.1371/journal.pone.0230197
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intestinal flora on the pharmacokinetics and pharmacodynamics of aspirin in high-altitude hypoxia

Abstract: Since hypobaric hypoxia significantly affects metabolic characteristics of intestinal flora, which plays an important role in the biotransformation of aspirin, high altitudes may influence the pharmacokinetics and therapeutic effects of aspirin in the intestines. In the present study, to test alterations of intestinal microbiota at high altitude comparing to that at low altitude, we analyzed rat feces from plain group and high-altitude group by 16S rRNA analysis. To detect concentrations of aspirin and salicyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 13 publications
2
15
0
Order By: Relevance
“…During environmental hypoxia in mice, the Bacteroidetes abundance increased at both the family and genus levels from days 1 to 14 in mice with hypoxia inducible factor-1 (HIF-1) deficiency in their bone marrow cells. This difference was significant compared with that of the wild-type group ( Han N. et al, 2020 ) and was consistent with previous findings that Bacteroidetes was more abundant in HIF-1-deficient mice than in wild-type mice ( Sun et al, 2020 ).…”
Section: Altitude-associated Hypoxia and The Gut Microbiotasupporting
confidence: 92%
“…During environmental hypoxia in mice, the Bacteroidetes abundance increased at both the family and genus levels from days 1 to 14 in mice with hypoxia inducible factor-1 (HIF-1) deficiency in their bone marrow cells. This difference was significant compared with that of the wild-type group ( Han N. et al, 2020 ) and was consistent with previous findings that Bacteroidetes was more abundant in HIF-1-deficient mice than in wild-type mice ( Sun et al, 2020 ).…”
Section: Altitude-associated Hypoxia and The Gut Microbiotasupporting
confidence: 92%
“…In addition, it may also offer us many innovative ideas of the drug delivery system design, especially the design of colon-targeted drug delivery systems. Herein, we provide a review to document the recent discoveries of the possible interactions of the gut microbiota, host and oral drugs by which the bioavailability may be affected (as shown in Table 1 24 , 25 , 26 , 28 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ) and make suggestions for further research in this field.…”
Section: Introductionmentioning
confidence: 99%
“… Possible mechanism Name Therapeutic application The influence on PK or pharmacological effects of the drug Ref. Prodrugs are metabolized by the gut microbiota Prontosil Antibacterial drug Activate the drug and the bioavailability is decreased when pretreated with antibiotics 30 , 31 Sulfasalazine Antibacterial drug Activate the drug and the bioavailability is decreased when pretreated with antibiotics 32 Lovastatin Lipid-lowering drug The bioavailability and pharmacological effects are decreased when antibiotics are used 33 The gut microbiota participates in its first-pass effect Deleobuvir Antiviral drug Plasma exposure of its major metabolite, CD 6168, is decreased substantially in pseudo-germ free rats 24 Amlodipine Cardiovascular drug for hypertension The systemic exposure of amlodipine is decreased 34 Nifedipine Cardiovascular drug for hypertension The bioavailability of nifedipine is increased when antibiotics are used or in the hypoxic condition 35 Aspirin Non-steroidal anti-inflammatory drug The bioavailability of aspirin is increased when antibiotics are used or after the quick ascent to the plateau 36 , 37 , 38 Microbial β -glucuronidases participate in the enterohepatic recirculation Mycophenolic acid Immunosuppressant AUC 0–12 h of the mycophenolic acid is decreased while CL of it is increased when pretreated with antibiotics 39 Indomethacin Non-steroidal anti-inflammatory drug The half-time is shortened and drug's systemic exposure is reduced when pretreated with antibiotics 25 The drug transport is affected by the modulations of bile acids induced by the gut microbiota Simvastatin Lipid-lowering drug Enhanced plasma concentration of simvastatin is p...…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have shown complex interactions between aspirin and gut flora. 2,3 We are particularly interested in the possible use of microbiota-based interventions to improve aspirin use for CRC prevention.…”
Section: Letter: Synergistic Role Of Gut Flora With Aspirin To Prevenmentioning
confidence: 99%
“…This showed a potential mechanism for the effect of aspirin in reducing colorectal cancer (CRC) risk and should inspire further studies. Other studies have shown complex interactions between aspirin and gut flora 2,3 . We are particularly interested in the possible use of microbiota‐based interventions to improve aspirin use for CRC prevention.…”
mentioning
confidence: 99%